PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN FISKUS DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK UMKM DI KANTOR PELAYANAN PAJAK PRATAMA MALANG UTARA) - Mirâ€™atusholihah, . (Jurnal Mahasiswa Perpajakan, 2014)
The low level tax compliance of small medium enterprises taxpayer caused the Government issued Government Regulation No. 46 Year 2013 on Income Tax on income derived by a taxpayer who has a circulation of 4.8 Billion Maximum Effort in 1 year. In addition, factors that may affect tax compliance is the knowledge of the procedures to meet tax obligations and knowledge about the function and role of taxes, on the other factors also affect the quality of service tax authorities on tax compliance. The population in this research are all taxpayers registered small and medium enterprisesÂ  in the North Malang service tax office until January 2014 in the amount of 3,967 taxpayers and the sample is calculated by Slovin formula in order to obtain 98 respondents. Based on the results of the F test is known that the knowledge of taxation, quality of service tax authorities and tax rates jointly have a significant effect on tax compliance. Meanwhile, based on the results of the t test is known that the knowledge of taxation partially significant effect on tax compliance, quality of service tax authorities partially insignificant effect on tax compliance and tax rates partially affect taxpayer compliance, but has a negative effect. Keywords: tax knowledge, Quality service of tax employee, tax rate, taxpayer compliance